The effect of hydrology on the distribution of ammonia-oxidizing betaproteobacteria in impounded black mangroves (Avicennia germinans) - Laanbroek, Hendrikus J.; Keijzer, Rosalinde M; Verhoeven, Jos T.A.; Whigham, Dennis F (Frontiers in Microbiology, 2012)
The distribution of species of aerobic chemolitho-autotrophic microorganisms such as ammonia-oxidizing bacteria are governed by pH, salinity, and temperature as well as the availability of oxygen, ammonium, carbon dioxide, and other inorganic elements required for growth. Impounded mangrove forests in the Indian River Lagoon, a coastal estuary on the east coast of Florida, are dominated by mangroves, especially stands of Black mangrove (Avicennia germinans) that differ in the size and density of individual plants. In March 2009, the management of one impoundment was changed to a regime of pumping estuarine water into the impoundment at critical times of the year to eliminate breeding sites for noxious insects. We collected soil samples in three different Black mangrove habitats before and after the change in management to determine the impacts of the altered hydrologic regimes on the distribution of 16s rRNA genes belonging to ammonia-oxidizing betaproteobacteria (β-AOB). We also sampled soils in an adjacent impoundment in which there had not been any hydrologic alteration. At the level of 97% mutual similarity in the 16s rRNA gene, 13 different operational taxonomic units were identified; the majority related to the lineages of Nitrosomonas marina (45% of the total clones), Nitrosomonas sp. Nm143 (23%), and Nitrosospira cluster 1 (19%). Long-term summer flooding of the impoundment in 2009, after initiation of the pumping regime, reduced the percentage of N. marina by half between 2008 and 2010 in favor of the two other major lineages and the potential ammonia-oxidizing activity decreased by an average of 73%. Higher interstitial salinities, probably due to a prolonged winter drought, had a significant effect on the composition of the β-AOB in March 2009 compared to March 2008: Nitrosomonas sp. Nm143 was replaced by Nitrosospira cluster 1 as the second most important lineage. There were small, but significant differences in the bacterial communities between the flooded and non-flooded impoundments. There were also differences in the community composition of the bacteria in the three Black mangrove habitats. N. marina was most dominant in all three habitats, but was partly replaced by Nitrosospira cluster 1 in sites dominated by sparsely distributed trees and by Nitrosomonas sp. Nm143 in sites characterized by taller, more densely distributed Black mangrove trees.